2021
DOI: 10.3126/jnps.v41i2.34916
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Diarrhoea: A Rare Presentation Of Vitamin B12 Deficiency Anemia In Children

Abstract: Vitamin B12 deficiency in children often under reported and usually presents with nonspecific manifestations like neuropsychiatric symptoms, anaemia, glossitis and chronic diarrhoea. Vegetarianism, minimal intake of animal products, poverty and malnutrition may lead to vitamin B12 deficiency. Laboratory reports often show pancytopenia, megaloblasts in bone marrow and low serum cynocobalamine. Injectable vitamin B12 is the treatment of choice. We would like to highlight this case report in view of vitamin B12 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…No diarrhea at admission and iron deficiency anemia at discharge were associated with lower B12 status. This is in line with previous studies among 6- to 35-month old Nepalese children [ 48 ] but not confirmed for children with diarrhea in the present study. In India, Kumar et al, (2018) also reported that vitamin B12 deficiency was low in children with persistent diarrhea, thrombocytopenia, and anemia [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…No diarrhea at admission and iron deficiency anemia at discharge were associated with lower B12 status. This is in line with previous studies among 6- to 35-month old Nepalese children [ 48 ] but not confirmed for children with diarrhea in the present study. In India, Kumar et al, (2018) also reported that vitamin B12 deficiency was low in children with persistent diarrhea, thrombocytopenia, and anemia [ 49 ].…”
Section: Discussionsupporting
confidence: 91%